ESP IN PRACTICE: EFFECTIVE STRATEGIES FOR TEACHING ENGLISH IN SPECIALIZED FIELDS - Iskenderova Kamola Azamatovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT This article examines the practical application of English for Specific Purposes (ESP)  in  teaching  English  tailored  to  the  linguistic  and  communicative  needs  of learners  across  various  professional  and  academic  disciplines.  Drawing  on contemporary research and theoretical frameworks, it discusses key teaching strategies, including  needs  analysis,  task-based  learning,  content-based  instruction,  authentic materials, and technology integration. The article also examines challenges faced by ESP practitioners and offers evidence-based recommendations for effective curriculum design and classroom practice. Findings indicate that ESP bridges the gap between general  English  proficiency  and  specialized  communication  competencies  in  fields such  as  medicine,  engineering,  business,  and  law.  The  study  concludes  that  ESP instruction  requires  innovative,  learner-centered  pedagogies  and  multidisciplinary collaboration to prepare learners for professional success.